Fostering Oral Chemotherapy Understanding and Safety (FOCUS) Project: Interventions for improving knowledge and compliance with national safety standards. Issue 28 (1st October 2022) - MacIntyre, Jessica; D'Aoust, Rita; Baker, Deborah; Hanson, Ginger; Gjolaj, Lauren Nicole; Swain Simpson, Chaitra; Negret, Lawrence M.; O'Neil, Daniel
Abstract : 370 Background: Oral chemotherapy drugs are not always subject to the same safety standards as intravenous chemotherapy. Variability in safety practices can cause gaps in care, creating a need for continuous review of this process. This quality improvement (QI) project sought to improve provider and staff general knowledge on oral chemotherapy and on national safety standards through an educational intervention and to evaluate the implementation of an electronic medical record (EMR) integrated chemotherapy documentation template geared towards improving compliance with national safety standards pertinent to oral treatment. Methods: We used a pre/post-test design to compare knowledge following an educational session. A 15-question test covering national guidelines and safety standards relevant to oral chemotherapy were used to evaluate base knowledge before and after the session. We compared pre and post-test scores using paired t-tests. Then, a chemotherapy documentation template was developed in the EMR. The medical records of 44 patients at the center were reviewed four months before and 44 patients one month after the template's introduction and documentation compliance was assessed using 24 national chemotherapy administration safety standards from the American Society of Clinical Oncology (ASCO) Quality Oncology Practice Initiative and the 2016 ASCO/Oncology Nursing Society Chemotherapy Administration Safety Standards. Comparison of compliance rates were performed using independent t-tests. Results: A total of 65 providers and staff participated in the educational session and completed both the pre and post-test. There was a statistical significance in knowledge gained from pre-test to post-test (p value of < 0.001). Additionally, from the 88 charts reviewed, there was a statistical improvement in compliance with national safety standards (p value of < 0.001). The participants (n = 29) also scored the documentation template as above average indicating overall ease of use and feasibility for continued use. Conclusions: This QI initiative improved provider knowledge and compliance with oral chemotherapy national safety standards. As a result, more centers should focus efforts on awareness and utilization of established national safety guidelines; critical to addressing the disparities in practice. Additionally, having a standardized workflow that prompts documentation within the EMR and discussion of the national standards is key to quality and safe practice.